Aplicação de métodos de simulação para a estimativa de recursos minerais - Luiz Alberto de Carvalho (2018)
For the success of a mining enterprise it is necessary to estimate and determine the size of the mineral reserves, a task of extreme relevance for mining. For this, there are several methods of resource estimation, among them the ordinary kriging is the method most used and conceptualized. In the last years with the technological advance, with the improvement in the computational processing capacity, the methods of simulation of geological models have been gaining spotlight, mainly for managing to fill some gaps left by deterministic methods. However, there is still a cultural barrier in the industry that acts as an impediment to the use of simulations. This work performed an analysis and comparison between ordinary kriging and turning band simulation, and also simulated the lithology of a mineral deposit through the multi-point simulation method. For its accomplishment, it used a database of an iron ore mine of the region of the Ferriferous Quadrangle. The results showed that the multi-point simulation presented good results regarding the simulation of the deposit, having a range of variation possibilities in its use. The comparison between ordinary kriging and turning bands simulation showed no significant difference between the methods, so that these results consolidate this simulation algorithm as a tool to estimate mineral deposit contents